Decoding the synergistic potential of herbal medicine and dietary supplements for treating postmenopausal osteoporosis - Jinfang Dou; Xuehong Hu; Junchang Liu; Jiaxian Liu; Chuyue Zhang; Yuelin Zhang; Xianjie Zhen; Siyu Tao; Jinghua Zhang; Guangjian Jiang (Experimental Gerontology)
Purpose: The exploration of the combined effects of FLL and quinoa presents an intriguing opportunity to enhance the efficacy of osteoporosis treatment. Methods: This study aimed to predict the potential anti-osteoporotic effects of FLL and quinoa using network pharmacology and subsequently verify these predictions through experimental investigation. Thirty rats were divided into five groups: sham operation group (SO), ovariectomized group (OVX), FLL group (FLL), quinoa group (Quinoa), and FLL combined with quinoa group (F&Q). The 12-week experiment involved measurements of bone density and microstructure, histological evaluation of femoral trabeculae and bone cortex, quantification of osteoclasts in the femur, assessment of osteoclast differentiation factor expression (NFATc1 and C-Fos), and measurement of collagen I carboxyl-terminal peptide (CTX-1). Additionally, intestinal flora analysis was performed. Results: The results demonstrated reduced bone mineral density, compromised bone microarchitecture, increased osteoclast numbers and differentiation, and enhanced bone resorption in the OVX group, which were completely ameliorated by FLL, quinoa and F&Q interventions. F&Q exhibited superior improvement in bone density and microarchitecture compared to FLL and quinoa, although no significant differences were observed in their effects on osteoclasts and bone resorption. Gut flora analysis revealed that F&Q was more effective than FLL and quinoa in alleviating OVX-induced intestinal flora disorders, particularly in terms of enhancing intestinal flora diversity and function. Conclusion: The combo of FLL and quinoa was more effective in treating ovariectomy-induced osteoporosis and gut flora dysbiosis than FLL alone.